Rapidly changing life history during invasion - Bøhn, Thomas; Sandlund, Odd Terje; Amundsen, Per-Arne; Primicerio, Raul (Oikos, 2004)
This is the peer reviewed version of the following article: Bøhn, T., Sandlund, O.T., Amundsen, P.‐A. & Primicerio, R. (2004), Rapidly changing life history during invasion. Oikos, 106 , 138-150, which has been published in final form at https://doi.org/10.1111/j.0030-1299.2004.13022.x . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions . The fish species vendace ( Coregonus albula ) invaded the sub‐arctic Pasvik watercourse during the second half of the 1980s, and became the dominant pelagic species in the upstream part of the watercourse within a few years. Life history traits of the pioneer population of vendace in Pasvik were recorded from 1991–2000. A rapid increase in population density in the upstream part of the watercourse was accompanied by decreased growth rates, decreased fecundity and a reduced size at first maturation. The downstream part of the watercourse showed a similar, but delayed, change in life history traits compared to the upstream part. The study documents great life history variability of a non‐native fish species entering a new environment. We discuss two co‐acting explanations for the observed patterns: (i) a density dependent response mediated by food depletion; and (ii) a pioneer strategy that allocates resources to favour reproduction at early developmental stages with a high number of offspring, trading off growth and size of offspring.